Enhancing business planning skills for women entrepreneurs in Kolhua Bazaar, Kupang City - Indri Astuti; Hironnymus Jati; Khalid K Moenardy; Bei Marselinus; Mahmud Ahmad (Community Empowerment, 2024)
The women members of the culinary bazaar face a challenge due to their limited knowledge, understanding, and skills in preparing business plans. This community service initiative aims to enhance their knowledge and understanding of crafting culinary business plans specifically for the Darul Hijrah Madani culinary bazaar group in Kolhua. Counseling, discussions, and training sessions were conducted with 20 bazaar members as part of this service activity. Analysis revealed a 75% increase in knowledge and an 83% improvement in understanding after counseling. Additionally, participants demonstrated a 60% proficiency in preparing business plans following the provided structure. These community service activities effectively enhance the knowledge, understanding, and skills of business actors in crafting business plans.